The application of Bacillus amyloliquefaciens and Arbuscular Mycorrhizal Fungi displays curative effects on Citrus Huanglongbing - Li, Yuning; Lin, Yigang; Liu, Zehua; Zeng, Maosheng; Xu, Hanhong (Frontiers in Plant Science, 2025)
Huanglongbing (HLB) is a severe citrus disease that results in significant yield loss, caused by the phloem-dwelling pathogen Candidatus Liberibacter asiaticus (CLas). Currently, antibiotics including penicillin, chloromycetin, and streptomycin are extensively utilized for the control of HLB in citrus production. However, various issues have emerged following the application of antibiotics, including the development of resistant microorganisms in soil and the accumulation of antibiotic residues in fruits. Consequently, there is an urgent need for alternative environmentally friendly methods for HLB control. In this study, the curative effects of Bacillus amyloliquefaciens strain HN11 and Arbuscular Mycorrhizal Fungi (AMF) on HLB were investigated. The HN11 strain and AMF demonstrated stable colonization within the interior of citrus roots. Moreover, HN11+AMF inoculation promoted the growth of HLB-infected citrus trees, accompanied by the decrease in CLas titers, reduction in H2O2 content, callus deposition, starch content, and ion leakage, as well as improvements in antioxidant enzyme activity indicators. The curative effects of HN11+AMF inoculation on HLB were also confirmed through field efficacy experiments. Moreover, HN11+AMF inoculation was identified to modify the composition and functions of root-soil bacterial and fungal microbial communities. These findings indicate that the use of HN11+AMF inoculation may serve as a promising control strategy for HLB management.